SHASHMAQOM AND WESTERN CLASSICAL MUSIC, A COMPARATIVE STUDY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the structural, semantic, and axiological similarities between Western Classical Music, the foundation of European art music, and Shashmaqom, the classical musical legacy of Central Asia. Both traditions have profound aesthetic, intellectual, and spiritual aspects despite having different cultural and historical roots. To show how each musical system reflects the worldview of its people, the study examines modal organization, improvisational strategies, and axiological implications.